KOMBINASI NEURO DEVELOPMENTAL TREATMENT DAN SENSORY INTEGRATION LEBIH BAIK DARIPADA HANYA NEURO DEVELOPMENTAL TREATMENT UNTUK MENINGKATKAN KESEIMBANGAN BERDIRI ANAK DOWN SYNDROME - Dzil Ikrom Al Hazmi, Dhofirul Fadhil; Tirtayasa, Ketut; Irfan, Muhammad (Sport and Fitness Journal; Volume 2, No.1, 2014)
One of health problem in child with special need is existed at birth (congenital), such as Down Syndrome. Child with down syndrome often get balance disturbance in stand which causes he cannot keep the body posture from the disturbance. This condition may causes the problem with his further motor development. There is neuro developmental treatment and sensory integration method in physiotherapy. The study aims to compare the combination of  neuro developmental treatment and sensory integration with neuro developmental treatment in child with down syndrome who get balance disturbance in stand. The study is an experimental research using randomized pre and post-test group design. The samples were 18 children with down syndrome which got balance disorder in stand. The study spent two months. There were two groups. The group one was treated using neuro developmental treatment and group two was used neuro developmental treatment and sensory integration. The Measuring instrument used  sixteen balance test which was included pre (0-session) and post (6-session) test for each subject. The descriptive data for both of groups are age: 2-4 years old children with down syndrome, sex: male and female, height: 70-85 cm and weight: 8-13 kg. The pre-test data of group one does not show normal distribution, but the post-test data shows normal distribution. Both of  pre-test and post-test data of  group two show normal distribution. According to compatibility test to both of groups, the hypothesis test used post-test data. The variable of sixteen balance test that used independent sample t-test both of groups which p value= 0,034. This study has two conclusions. First conclusion is got from the percentage of static sixteen balance test variable which  shows p value < 0,05. The value illustrates that the using the combination of neuro developmental treatment and sensory integration is better than just using neuro developmental treatment to improve  the balance of stand.
Keywords: neuro developmental treatment, sensory integration, down syndrome, the balance of stand, sixteen balance test.